2009
DOI: 10.1007/s10571-009-9358-6
|View full text |Cite
|
Sign up to set email alerts
|

New Age of Neuroproteomics in Alzheimer’s Disease Research

Abstract: Alzheimer's disease (AD) is the leading cause of dementia, a condition that gradually destroys brain cells and leads to progressive decline in mental functions. The disease is characterized by accumulation of misfolded neuronal proteins, amyloid and tau, into insoluble aggregates known as extracellular senile plaques and intracellular neurofibrillary tangles, respectively. However, only tau pathology appears to correlate with the progression of the disease and it is believed to play a central role in the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 60 publications
0
10
0
3
Order By: Relevance
“…To determine the consequences of tau pathology, both in animal models and human disease, we and others have applied the tools of functional genomics [4]. Proteomic analysis, e.g., revealed separate and synergistic modes of Aβ and tau on mitochondrial functions [5], [6] while in a transcriptomic study, we identified the detoxifying enzyme glyoxalase I as a target of tau toxicity [7].…”
Section: Introductionmentioning
confidence: 99%
“…To determine the consequences of tau pathology, both in animal models and human disease, we and others have applied the tools of functional genomics [4]. Proteomic analysis, e.g., revealed separate and synergistic modes of Aβ and tau on mitochondrial functions [5], [6] while in a transcriptomic study, we identified the detoxifying enzyme glyoxalase I as a target of tau toxicity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of Alzheimer disease are sporadic and idiopathic; however, mutations in three genes, APP, presenilin 1 and presenilin 2 have been identified as being responsible for a small fraction of early-onset Alzheimer disease, that accounts for approximately 5% of all Alzheimer disease cases. With increasing life-span and in the absence of interventions to slow or arrest progression of AD, the number of elderly people at risk of developing dementia is growing rapidly [11]. Large number of studies proposed various hypotheses to explain the pathogenesis or progression of sporadic AD that include the amyloid hypothesis, the oxidative stress hypothesis and APOE genotype among others [1217].…”
Section: Introductionmentioning
confidence: 99%
“…Other processes, such as oxidative damage to DNA and RNA, have also been implicated in the pathogenesis of AD [11], as well as lesion histogenesis [1215]. Still others suggest tau protein metabolism as the rate-limiting factor in disease, specifically phosphorylation, conformational changes and cleavage [1621]. A number of other mechanisms have been implicated, including such general mechanisms as apoptosis, inflammation and excitotoxicity.…”
mentioning
confidence: 99%